Farmers’ Market Fraud: California’s Approach and What It Means for Farmers’ Market Regulation - Marketich, Nathan J. (Journal of Law and Commerce, 2016)
The United States Department of Agriculture (“USDA”) defines a farmers’ market as “a multi-stall market at which farmer-producers sell agricultural products directly to the general public at a central or fixed location, particularly fresh fruit and vegetables (but also meat products, dairy products, and/or grains).”[1] The recent resurgence in the popularity of farmers’ markets represents a return to days past where local producers were the predominant source for fresh produce and agricultural goods. With the most farmers’ markets of any state,[2] California has a large interest in the success of its farmers’ markets. In furtherance of this interest, California endeavors to protect its farmers’ markets from fraud.[3] Prior to 2015, California had one of the strictest farmers’ market regulatory programs in the United States.[4] Even so, the California legislature decided that more needed to be done in order to prevent farmers’ market fraud and on September 26, 2014 enacted Assembly Bill 1871 (“A.B. 1871”).[5] The primary function of this Note is to analyze A.B. 1871 and develop an understanding of the California model for regulation of farmers’ markets. This model will be compared to the approaches taken by New York and Michigan (states with the second and third most farmers’ markets)[6] to develop a greater understanding of the various approaches to farmers’ market regulation. The goal of this Note is to serve as a policy guide for farmers’ market regulation. Following this introduction, this Note will proceed in six parts. Part I will discuss the recent history of farmers’ markets with a particular emphasis on the economic and social impact that farmers’ markets have on the communities in which they operate. Part II addresses the nature of farmers’ market fraud and some general ways that states and farmers’ market vendors and operators combat fraud. Part III will provide a comprehensive analysis of A.B. 1871 and its components. Part IV will provide a comparative analysis of the regulatory approaches taken by New York and Michigan. Part V outlines four general factors for states to consider before enacting statewide regulations for farmers’ markets. Finally, Part VI concludes with guidance on state policy regarding regulation of farmers’ markets. [1] What is a Farmers’ Market?, USDA Food & Nutrition Serv., (May 27, 2015), http://www.fns.usda.gov/ebt/what-farmers-market. This Note will adhere to this definition of “farmers’ market,” and any reference to “farmers’ market,” unless specifically stated otherwise, is intended to reference this definition. [2] National Farmers Market Directory, USDA Agric. Mktg. Serv., http://search.ams.usda.gov/farmersmarkets/ (last visited February 1, 2015). As of January 2015, California had over 760 farmers’ markets registered with the USDA. The USDA’s Agricultural Marketing Service (“AMS”) collects farmers’ market information and numbers through voluntarily submitted data. Id. [3] For the purposes of this Note, farmers’ market “fraud” indicates whenever a vendor sells something that the vendor did not produce, cultivate, or harvest himself/herself and/or a vendor misrepresents something as being from a local area. A discussion on the nature of farmers’ market fraud is contained infra, Part II. [4] Samuel R. Wiseman, Emerging Issues in Food Law: Fraud in the Market, 26 Regent U. L. Rev. 367, 386 (2013-2014) (discussing California’s previous system of farmers’ market regulation). [5] A.B. 1871, 2014 Cal. State Assemb., Reg. Sess. (Cal. 2014). [6] National Farmers Market Directory, supra note 2.